2020
DOI: 10.1021/acsami.0c10118
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Cr2WO6-Modified WO3 Nanowires with a Large Specific Surface Area and Rich Lewis Acid Sites: A Highly Efficient Catalyst for Oxidative Desulfurization

Abstract: The oxidative desulfurization (ODS) of fuel oils is of great significance for environmental protection, and the development of efficient ODS heterogeneous catalysts is highly desired. Herein, we have designed and synthesized a novel material of amorphous Cr2WO6-modified WO3 (a-Cr2WO6/WO3) nanowires (3–6 nm) with a large specific surface area of 289.5 m2·g–1 and rich Lewis acid sites. The formation of such a unique nanowire is attributed to the adsorption of Cr3+ cations on non-(001) planes of WO3. In the ODS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…As depicted in Table 1, due to the load of a-Fe 2 O 3 , the specific surface area of the La 0.7 Sr 0.3 MnO 3 /a-Fe 2 O 3 (20%) increased significantly from 9.97 m 2 g -1 to 63.92 m 2 g -1 , which helps to improve its adsorption capacity. It indicates that the composite could be an efficient photocatalyst, and it will exhibit high activity owing to its high specific surface area [31].…”
Section: Bet Analysismentioning
confidence: 99%
“…As depicted in Table 1, due to the load of a-Fe 2 O 3 , the specific surface area of the La 0.7 Sr 0.3 MnO 3 /a-Fe 2 O 3 (20%) increased significantly from 9.97 m 2 g -1 to 63.92 m 2 g -1 , which helps to improve its adsorption capacity. It indicates that the composite could be an efficient photocatalyst, and it will exhibit high activity owing to its high specific surface area [31].…”
Section: Bet Analysismentioning
confidence: 99%
“…Additionally, the SSA of NMO-30 (43.5 m 2 g –1 ) is smaller than that of NMO-10 (62.7 m 2 g –1 ), while NMO-30 exhibits superior desulfurization efficiency to NMO-10, which illustrates that oxygen vacancies may play the main role in accelerating the ODS reaction. Furthermore, several similar representative ODS systems are listed for comparison (Table S2), it is observed that YS-V O -NMO can achieve ultradeep desulfurization under relatively mild reaction conditions (O/S = 5, T = 60 °C), indicating that it has appeared in the front ranks of the existing catalysts. , …”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may be caused by the fact that excessive H 2 O 2 added into the reaction system brings about more water, which limits the mass transfer and weakens the solubility of DBT in [OMIM]BF 4 due to the diluted extractant phase. 15 Considering that alkyl-substituted dibenzothiophenes including 4-MDBT and 4,6-DMDBT also exist in real oils, it is necessary to investigate the desulfurization efficiency of model oil systems containing them. As shown in Figure 5d, DBT and 4-MDBT can be almost removed from the oil after 70 min of reaction, while the sulfur removal of 4,6-DMDBT can only reach 94.6% under the same conditions.…”
Section: Catalytic Ods Performancementioning
confidence: 99%
See 1 more Smart Citation
“…However, due to its severe operating conditions in terms of high reaction temperature and pressure, HDS has high operating costs and is less effective in eliminating refractory sulfur compounds; hence, it may not be the optimum desulfurization process [19,20]. Recently, sophisticated technologies such as catalytic oxidative desulfurization (Cat-ODS), selective adsorption, biodesulfurization, and oxidation-extraction have been used for the production of ultralow-sulfur fuels [21][22][23]. Cat-ODS has proven to be one of the most potent recent alternatives to HDS [24,25].…”
Section: Introductionmentioning
confidence: 99%